Utilization of mechanically recovered poultry meat in the production of shelf-stable chicken hotdog - Lim, Janice Jeza A. (2003)
ABSTRACT This study aimed at the development of shelf-stable MRPM-based chicken hotdog. From the focus group discussions, a highly acceptable chicken hotdog has the following characteristics: red in external color, regular size, with no visible air spaces, slightly greasy, with distinct chicken flavor, juicy, and tender. To arrive at the desired qualities, modifications were done on the basic hotdog formulation, specifically addition of ginger powder and extender and reduction of the amount of water. Results of the paired preference test suggested that the modified formulation did not differ significantly from the original, thus, for economic reasons, the original was chosen to undergo the next phase. On the 2nd and 8th day post-production, microbiological analysis was done on raw samples stored at -15 to -20°C to determine the proper proportion of antimicrobials to improve shelf-life of the product. Among the four formulations with varying proportions of antimicrobials, the second variation was the most effective as there were no counts for coliform and S. aureus. The total plate counts were within the acceptable range, <10^6 cfu/g sample. Based on the mean scores, the four formulations had statistically the same degree of acceptability corresponding to "like slghtly", but the control was notably liked the least. Proximate analysis of the raw and cooked samples of Formulation 2 showed that the hotdog is relatively high in moisture, fat and protein contents, but had minimal fiber and total available carbohydrate while its ash content was slightly higher compared to similar types of hotdog.